CERITA RAKYAT “SI LANCANG” DARI INDONESIA, DENGAN CERITA RAKYAT “NAHKODA MANIS” DARI BRUNEI, DAN CERITA RAKYAT “SI TANGGANG” DARI MALAYSIA; SEBUAH KAJIAN STRUKTURAL SASTRA BANDINGAN - aisyah labibah (RUANG KATA: Journal of Language and Literature Studies, 2022)
Mother's love doesn't matter, for the sake of her child she is willing to do anything. Including to support the decision of the child who wants to migrate to improve the family economy. A child who went abroad became successful because of his business outside the city and then forgot his mother who was alone at home praying for her child's safety. Although this story has often been heard by the people of Indonesia, it is about a child who disobeys his mother. However, it turns out that this theme is not only found in Indonesia. There are several folk tales with the same theme from various countries, such as Malaysia and Brunei. This is interesting to study because the three folklores are located in different areas with different socio-cultural and economic backgrounds, but have similarities or parallels in story motifs. This study aims to determine the similarities and differences between the folklore "Si Lancang" from Riau, Indonesia, with the story "Nakhoda Manis" from Brunei, and the folktale "Si Tanggang" from Malaysia. The study used in this research is a comparative literary structure study. This study uses a comparative description method. Through comparative literary structural studies, it can be said that these folk tales have similarities in structures such as themes and messages. There are also differences in characters, characteristics, plots, and folklore backgrounds. Keywords: Comparison, structural, folklore.